Evaluation of Rosenmuller Fossa with cone beam computed tomography: A retrospective radio-anatomical study - Fatma Akkoca Kaplan; İbrahim Şevki Bayrakdar; Elif Bilgir (Selçuk University, 2019)
Background: Rosenmuller fossa (RF) is known as a lateral pharyngeal recess, is bilaterally located beneath the skull base and behind the torus tubarius. Nasopharyngeal carcinoma is most commonly located in the RF. The purpose of this study is to evaluation of RF with cone beam computed tomography Methods: A total of 150 subjects (80 females, 70 males, 6-88 years) were included in the study. Subjects were divided into age groups (6- 20 years, 21-30 years, 31-40 years, 41-50 years, 51-60 years, over 60 years) and gender. Result: There is no statistically significant difference between class (RF type) and gender (p = 0.086). There is a statistically significant association between the categories of age group and class variables (p = 0.015). RF type 1 was more common in the 6-20 age and 21-30 age groups, whereas RF type 3 was more common in the 41-50 age and 51-60 age groups. Conclusion: When the literature was investigated, it was not found a study evaluating RF with cone beam computed tomography. When considering clinical significance, RF should be searched and examined in larger populations. KEYWORDS  Cone beam computed tomography, Rosenmuller  Fossa, Nasopharyngeal Carcinoma